Effect of Climatic and Thermal Aging on Friction of Frost-Resistant Rubber With and Without Ultra-High Molecular Weight Polyethylene Coating - Ivan Shkalei; Jeng-Haur Horng; Elena Torskaya; Pavel Bukovsky; Aleksey Morozov; Fedor Stepanov; Natalia Petrova; Afanasy Dyakonov; Vasilii Mukhin (Coatings, 2025)
The polymer composite frost-resistant rubber–UHMWPE (ultra-high molecular weight polyethylene) has simultaneously damping, anti-wear and anti-friction properties. To use it in seals operating in northern climatic conditions, it is necessary to study the effect of climatic aging on mechanical, strength and tribological properties of the composite. In this study, climatic aging of rubber and UHMWPE separately was made at testing ground in Yakutsk (Russia), as well as accelerated thermal aging of the composite in laboratory conditions. Comparison of the results of climatic and laboratory aging showed that climatic aging has a negative effect on the properties of both rubber and UHMWPE. Accelerated aging, on the contrary, leads to an improvement in the anti-friction properties of the composite with a small (about 10 percent) increase in its stiffness. Thus, with prolonged use in friction units, the composite should be protected from radiation and ozone.